水润滑复合材料齿轮非稳态热弹流润滑分析 - 付小芯; 申立涛; 王优强 (Jixie chuandong)
The composite material gear is manufactured with modified PEEK materia1.The transient thermal EHL solution of composite material gear is obtained by numerical simulation analysis in water lubrication conditions.The simulation result of the composite material gear is compared with that of the isothermal solutions.The results show that the meshing water film pressure by the influence of the temperature of is small,the film thickness of the approach action point side is thinner than the isothermal solutions and it is opposite in the recess action point side.